Studies of the decay D s + → K + K − μ + ν μ $$ D_{s}^{+}→ K^{+}{K}^{-}{μ}^{+}{ν}_{μ } $$ - The BESIII collaboration; M. Ablikim; M. N. Achasov; P. Adlarson; X. C. Ai; R. Aliberti; A. Amoroso; M. R. An; Q. An; Y. Bai; O. Bakina; I. Balossino; et al. (Journal of High Energy Physics, 2023)
Abstract The D s + → K + K − μ + ν μ $$ D_s^{+}→ K^{+}{K}^{-}{μ}^{+}{ν}_{μ } $$ decay is studied based on 7.33 fb −1 of e + e − collision data collected with the BESIII detector at center-of-mass energies in the range from 4.128 to 4.226 GeV. The absolute branching fraction is measured as B D s + → ϕ μ + ν μ = 2.25 ± 0.09 ± 0.07 × 10 − 2 $$ \mathcal{B}\left(D_s^{+}→ φ μ^{+}{ν}_{μ}\right)=\left(2.25± 0.09± 0.07\right)× {10}^{-2} $$ , the most precise measurement to date. Combining with the world average of B D s + → ϕ e + ν e $$ \mathcal{B}\left(D_s^{+}→ φ {e}^{+}{ν}_e\right) $$ , the ratio of the branching fractions obtained is B D s + → ϕ μ + ν μ B D s + → ϕ e + ν e = 0.94 ± 0.08 $$ \frac{\mathcal{B}\left(D_s^{+}→ φ μ^{+}{ν}_{μ}\right)}{\mathcal{B}\left(D_s^{+}→ φ {e}^{+}{ν}_e\right)}=0.94± 0.08 $$ , in agreement with lepton universality. By performing a partial wave analysis, the hadronic form factor ratios at q 2 = 0 are extracted, finding r V = V 0 A 1 0 = 1.58 ± 0.17 ± 0.02 $$ {r}_V=\frac{V(0)}{A_1(0)}=1.58± 0.17± 0.02 $$ and r 2 = A 2 0 A 1 0 = 0.71 ± 0.14 ± 0.02 $$ {r}_2=\frac{A_2(0)}{A_1(0)}=0.71± 0.14± 0.02 $$ , where the first uncertainties are statistical and the second are systematic. No significant S-wave contribution from f 0(980) → K + K − is found. The upper limit B D s + → f 0 980 μ + ν μ ⋅ B f 0 980 → K + K − < 5.45 × 10 − 4 $$ \mathcal{B}\left(D_s^{+}→ {f}_0(980)μ^{+}{ν}_{μ}\right)· \mathcal{B}\left({f}_0(980)→ K^{+}{K}^{-}\right)<5.45× {10}^{-4} $$ is set at 90% credibility level.